Refleksi Sosial Dalam Novel Down and Out In Paris and London Karya George Orwell: Kajian Sastra Marxisme - Rizki Rabiul Tsani; Fenty Sukmawaty; Siska Hestiana (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research is entitled Social Reflection in the novel Down and Out in Paris and London by George Orwell: Study of Marxism Literature. The purpose of this research is reflect social impression to found in the novel Down and Out in Paris and London By George Orwell trough Study of Marxism Literature. Descriptive qualitative is the method which applied in this research, and trough sociology approach of marxism literature. In generally, this research discusses what it was like to live poor, he himself was never really poor, considering that after all he came from a fairly well-off family that could be the last resort in the worst case. The novel Down and Out in Paris and London tells the story of Orwell's experience of living in poverty while in Paris and then in London. While in Paris this is the beginning of the story begins, Orwell began to be forced to live in poverty. Then, feeling unable to work as a dishwasher in Paris, he moved to London, and in that city his story of poverty continued with new friends, with new miseries. This research collected data by using the technique of read and record. While specifically, the data in this research present data related to social construction and historis materialism based on study of marxism literature trough social aspect, background social, and plot contained in the novel Down and Out in Paris and London by George Orwell.